Fetal intracranial structures: differences in size according to sex - Kavak, Ebru Celik; Kavak, Salih Burcin; Sanli, Cengiz; Batmaz, Ibrahim; Ozden, Seren; Sapmaz, Ekrem (Walter de Gruyter Gmbh, 2021)
Objectives: We aimed to compare gender difference on sizes of some structures in the brain of normal male and female fetuses between 20 and 22 week gestations. Methods: A total of 300 female and 300 male singleton pregnancies with low risk were included in the study. Biparietal diameter, head circumference, transcerebellar diameter, cisterna magna, nuchal fold thickness, anterior and posterior horn of lateral ventricles, length and width of cavum septum pellucidum were measured trans-abdominally. Mean +/- SD values were calculated and comparison of measurements were done between male and female fetuses. Kolmogorov-Smirnov and independent samples t-test were used for statistical analysis. A value of p<0.05 were accepted as statistically significant. Results: We determined statistically significant difference in sizes of some structures of the brain of male and female fetuses. Mean +/- SD value of cavum septi pellucidi width was 3.38 +/- 0.61 and 3.85 +/- 0.96 in female and males, respectively (p<0.05). Male fetuses were also found to have larger anterior (1.92 +/- 0.30 vs. 1.58 +/- 0.26, p<0.0001) and posterior horn of lateral ventricles (6.00 +/- 0.87 vs. 5.53 +/- 1.17, p<0.05). Conclusions: Difference in sizes of some structures of the brain starts in fetal life. This finding may be important in evaluating the intracranial structures more precisely. These results may also give a contribution to the understanding physiological and pathologic differences between males and females.
Keywords: fetal brain; gender differences; second trimester screening